Effects of a formal mentoring program on teacher retention and benefits to proteges and mentors - Hope, Larry Lloyd (2001)
This thesis is an evaluation research study into the effects of a formal mentoring program on teacher retention and the benefits to mentors and protégés. The program studied took place in the Keewatin-Patricia District School Board in Northwest Ontario during the 1999-2000 school year, and involved the collection and subsequent examination of experiential data collected from participants in the program. The respondents included experienced teachers who served as mentors and new or beginning teachers who were the protégés. A review of the literature outlined the benefits to mentors and protégés as well illuminated such issues as mentor selection and training and descriptions of several other mentoring programs. Further, characteristics of mentor teachers are discussed. The data collected are coded into categories based on benefits to mentors from a personal as well as a professional viewpoint. Benefits to protégés are discussed in terms of qualities of mentor teachers, technical support provided, and communication between mentors and protégés. Teacher retention is defined by school board statistics relating to the number of beginning teachers who made the decision to continue teaching with the school board the following year.